Microstructure evolution of third generation nickel-based single crystal superalloy DD10 after long-term aging - ZHEN Xingmin; ZHAO Jie; CAO Tieshan (Cailiao gongcheng)
A comprehensive long-term aging study has been conducted on the third-generation nickel-based single-crystal superalloy DD10 at temperatures of 900 ℃ and 1050 ℃. This investigation systematically analyzes the microstructural evolution disparities between dendrite regions， as well as the evolution of the distribution characteristics of the γ' phase and TCP phase under various aging conditions. The results indicate that during aging at 900 ℃， the γ' phase undergoes gradual coarsening and growth with increasing aging time. Conversely， at 1050 ℃， the γ' phase coarsens rapidly and retains a cubic shape after 100 h of aging. The trend of γ' phase coarsening and growth is consistent between dendrite regions， with minimal difference in the average size of the γ' phase within these regions under the same aging duration. Quantitative statistical analysis reveals that the coarsening of the γ' phase aligns with the Lifshitz-Slyozov-Wagner （LSW） model. Following aging at 1050 ℃ for 500 h or more， the γ' phase within the dendritic core adopts an irregular shape， and stress within the dendrites leads to the formation of a valuated structure in the γ' phase between dendrites， with the valuation direction coinciding with the primary dendrite growth direction ［001］. During aging at both 900 ℃ and 1050 ℃， TCP phase precipitation between dendrites is minimal， whereas the TCP phase volume fraction within dendrite stems increases significantly with increasing temperature and time. After aging at 1050 ℃ for 2000 h， the TCP phase volume fraction reaches 8.25%. Compositional analysis suggests that the TCP phase is likely the μ phase. Equilibrium phase diagram calculations confirm the precipitation of the μ phase in the alloy at the experimental temperatures， and TTT curve calculations indicate that the time required to precipitate the same volume fraction of μ phase is longer at 900 ℃ compared to 1050 ℃.